ASPECTS OF CULTURAL TOURISM IN BRAȘOV COUNTY WITH A SPECIAL LOOK AT THE PERIOD 2015-2016 - Daniela-Mirela PLEȘOIANU; Cristiana SANDU; Agatha POPESCU (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
As a branch of touris, cultural tourism has seen a tremendous development and diversification, both at European and international level, as a result of political and economic opening in the countries of Central and Eastern Europe on the one hand and, on the other, due to the competition between the countries with old traditions in this form of tourism. The purpose of the paper was to point out that cultural tourism remains one of the most important forms of tourism practiced in Brasov city and county, which contributes both to the economic development of the area and to a better knowledge of the Romanian values in general both within the country and at international level. The data were provided by Brașov County Council, the Brașov County Development Strategy 2007 - 2013, and National Institute of Statistics, Brașov branch. They were processed and converted into tables, graphs and then interpreted and analyzed. Of the total tourist accommodation units in operation, the hotels occupied 42.7%, agrotourism pensions 20.9%, tourist pensions 18.1%, tourist villas 5.9%, tourist cottages 4.0%, hostels 4%, motels 2.5%, campings 1.4%, and other types of reception structures 1.1%. As a result of 771 tourist activities, it is noticed that the number of tourists arrived in September 2016 was 108,308 persons, of which 83,299 Romanian tourists (76.9%), and 25,009 nonresident tourists (23.1%). In January-September 827,574 tourists (82.4% Romanians and 17.6% foreigners) recorded a 10.3% increase compared to January-September 2015. Regarding the origin of the tourists, the most numerous are from Germany, 1,006, registered in March 2016, followed by Spain, with 816 and Israel, 793. The least numerous come from Russia, arriving especially during the winter holidays.